2020
DOI: 10.31838/ijpr/2020.12.02.359
|View full text |Cite
|
Sign up to set email alerts
|

Identify Human Cluster of differentiation 147 (CD147), a New Target of SARS-CoV-2 Invasion

Abstract: Objective: to determine the level of blood markers of cellular Human Cluster of Differentiation 147 (CD147) by ELISA assay. Immunological system, establishing the profile in patientsSARS-CoV-2 invades host cells via a novel route CD147-spike protein. Methods: a case-control study including 30 patients (10 female) with SARS-CoV-2 repertory disorder whose follow-up was carried out at the outpatient clinic of the intensive care unit Service at Al Hussain Hospital, southern of Iraq, Patients were divided into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Red blood cells (RBC) are the carriers of oxygen throughout the body and are known to lyse in cases of infection ( Bouchla et al, 2022 ), especially with the increasing complications of sepsis ( Bateman et al, 2017 ). Previous studies have shown that the virus can invade erythrocytes by interacting its S1 spike protein with erythrocyte CD147 ( Al-Salih et al, 2020 ) and the band-3 protein ( Cosic et al, 2020 ). However, viral spike proteins and complement activation products have been detected on the cell surface of erythrocytes from patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Red blood cells (RBC) are the carriers of oxygen throughout the body and are known to lyse in cases of infection ( Bouchla et al, 2022 ), especially with the increasing complications of sepsis ( Bateman et al, 2017 ). Previous studies have shown that the virus can invade erythrocytes by interacting its S1 spike protein with erythrocyte CD147 ( Al-Salih et al, 2020 ) and the band-3 protein ( Cosic et al, 2020 ). However, viral spike proteins and complement activation products have been detected on the cell surface of erythrocytes from patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%